Investigation of A Multiple Sclerosis Patient According to The Behavioural System Model of Dorothy Johnson: A Case Example - Kubra OYMAAGACLIO; Bilgi GULSEVEN KARABACAK (Atatürk University, 2021)
Nursing theories and models play an important role in providing holistic nursing care based on scientific foundations. Theories and models are important and guiding in chronic disease management, nursing care planning, nursing practice and research. Improves the quality and effectiveness of care. The number of models published in the field of nursing from the past to the present and proven to be applicable is increasing day by day. The application of these theories and models in different fields, enriching the relevant examples and reflecting them to the nursing care by being concrete will be effective in the nurses' holistic approach to patient care from a different perspective. The Behavioral System Model developed by Dorothy Johnson suggests that the individual has two systems, both biological and behavioral. The behavioral system includes seven subsystems. These; It is a subsystem of commitment (close relationship), defense (protective), dependence, excretion, nutrition, sexuality and achievement. According to this model; the nurse treats the individual as a whole, focuses on the individual's behavior change and is responsible for ensuring the balance of the subheadings in the system. In the literature review, it was observed that both the studies on Dorothy Johnson's model and the literature on the use of theories and models in the care of patients with multiple sclerosis were limited. In this study, the care process of a patient with multiple sclerosis was planned based on Dorothy Johnson's Behavioral System Model. This case report, which was formed by using the Behavioral System Model, was prepared after verbal and written consent was obtained from a patient with multiple Sclerosis who was treated as an outpatient in the neurology sub-clinic of an educational research hospital in the European side of Istanbul.